2019
DOI: 10.1186/s40104-019-0317-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplementation with n-3 polyunsaturated fatty acids and/or β-glucans on performance, feeding behaviour and immune status of Holstein Friesian bull calves during the pre- and post-weaning periods

Abstract: BackgroundPrevious research in both calves and other species has suggested n-3 polyunsaturated fatty acids (PUFA) and β-glucans may have positive effects on immune function. This experiment measured performance, behaviour, metabolite and immunological responses to pre-weaning supplementation of dairy bull calves with n-3 PUFA in the form of fish oil and β-glucans derived from seaweed extract. 44 Holstein Friesian bull calves, aged 13.7 ± 2.5 d and weighing 48.0 ± 5.8 kg were artificially reared using an electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 61 publications
(123 reference statements)
1
14
0
Order By: Relevance
“…Furthermore, Benson et al (55) reported that dairy cows infused, via the abomasum, with a mixture of sunflower and rapeseed oils did not alter their daily time spent engaged in eating, ruminating and idling activities. Similarly, McDonnell et al (56) found that feeding behaviour of bull calves was not altered with fish oil supplementation during the preweaning period.…”
Section: Effect Of Preweaning Dietsmentioning
confidence: 91%
“…Furthermore, Benson et al (55) reported that dairy cows infused, via the abomasum, with a mixture of sunflower and rapeseed oils did not alter their daily time spent engaged in eating, ruminating and idling activities. Similarly, McDonnell et al (56) found that feeding behaviour of bull calves was not altered with fish oil supplementation during the preweaning period.…”
Section: Effect Of Preweaning Dietsmentioning
confidence: 91%
“…McDonnell et al (39) have noted a reduction in starter intake in calves that received FO supplemented through milk replacer. With respect to the individual FAs, our results show an increase in dietary consumption of specific FA in experimental animals compared to the control group (linoleic and linolenic acid in the SBO diet and EPA and DHA in the FO diet).…”
Section: Intake Of Starter and Individual Fasmentioning
confidence: 97%
“…McDonnell et al (39) have reported a significant increase in plasma levels of EPA and DHA in calves fed FO supplemented milk replacer compared to a control group. Lower inflammatory signs in FO supplemented calves can be related to higher long-chain PUFA contents of the plasma (39,41) .…”
Section: Blood Metabolites Fa Profiles and Inflammatory Markersmentioning
confidence: 98%
See 1 more Smart Citation
“…56 In a recent study replacing 2% of the total DM with fish oil fed to preweaned calves did not reduce the serum haptoglobin concentrations or mitogen-induced interferon-g secretion. 58 In contrast, Garcia and colleagues 60 supplemented preweaned calves with either a low or high omega-6 linoleic acid milk replacer (0.46% or 9.0% of the total fatty acids, respectively) and reported that the high linoleic acid treatment had many differentially expressed genes in the liver that should predict a reduced risk of infection. The linoleic fatty acid compositions used in the study of Garcia and colleagues likely reflect milk diets based on milk fat (low linoleic acid) and those in which the primary fat source is based on lard (high linoleic acid).…”
Section: Polyunsaturated Fatty Acidsmentioning
confidence: 99%